The effect of design capability characteristic on design performance for Bumiputera furniture companies - Osman, Nur Syazana; Abd Rahman, Khairul Aidil Azlin; Abdul Rahman, Ahmad Rizal; Ja’afar, Mohd Fakri Zaky (RMP Publications, 2018)
Malaysia furniture industry has seen exchange from the Original Equipment Manufacturer (OEM) to Original Design Manufacturer (ODM). These changes occur due to the local furniture manufacturers to add design value into their products. One of the ways out of this creativity rut was to revamp the model form producing or manufacturing product for international buyers in creating, designing and marketing our own product internationally. This study attempts to investigate the design capability of Bumiputera furniture manufacturing companies, that effects on the decline on design performance. Besides that, this paper also is to develop a richer understanding of how design capability can be introduced, accepted and sustained in the organization. 30 questionnaire survey was sent out to design managers or CEO of Bumiputera furniture manufacturing companies, and empirically demonstrate that both design and process management have an equal impact on design performance. This study uses a literature review and data collection from structured interview to document the findings. Then, it uses a data analysis (SPSS) to identify the appropriate components as design capability characteristics in developing the framework model. The framework model is to provide details of effects and actions on the companies, in order them to enhance their design performance. The finding shows the Bumiputera companies need to improve and enhance their design and process management with long-term implementation, in order to achieve the companies goal. With understanding the aspect of design capability, future efforts to develop the design capability become more successful and help to decrease the risk of design development.